Field efficacy of botanical extracts for controlling major insect pests of Okra (Abelmoschus esculentus) - ADIROUBANE, D; LETCHOUMANANE, S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1994 to evaluate efficacy of 3 plant extracts viz, sacred basil (Ocimum sanctum L.), Malabar nut (Adhatoda vesica Nees), Chinese chaste tree (Vitex negunda L.) and synthetic insecticides, viz endosulfan and carbaryl, and their combination products in controlling okra jassids, Amrasca biguttula biguttula (Ishida) and fruit-borers, Earias spp during rainy season (kharif) 1994 by spraying them at 10,25 and 40 days after sowing. All the treatments suppressed both the jassids population and fruit borer incidence.